The Impact of Country Personality Dimensions on Country Attractiveness and Word-of-Mouth: A Cambodian Tourism Case - Traikasem, Sirintip; Polyorat, Kawpong (Connexion: Journal of Humanities and Social Sciences, 2017)
Conceptualizing a country as a brand, which requires a marketing promotion, can lead to the idea of relating personality to a country. The current study thus focuses on the dimensions of country personality traits on country attractiveness and word-of-mouth in terms of tourism. A survey was conducted with a sample of Thai undergraduate students and Cambodia as the country context. Data were analyzed by a multiple regression in order to explore the relationship among country personality traits, country attractiveness and word-of-mouth. Results reveal that only the competence and sophistication country personality dimensions significantly impact country attractiveness and word-of-mouth. Furthermore, country attractiveness also partially mediates the influence of the sophistication dimension and fully mediates the influence of the competence dimension on word-of-mouth. These findings provide stakeholders in tourism business, both in public and private sectors, a better understanding of country personality so that they can create a marketing campaign for a country by positioning an appropriate country personality.